Cyber Attacks on Commercial Drones: A Review - Bruno Branco; Jose Silvestre Serra Silva; Miguel Correia (IEEE Access)
s, also known as drones, are increasingly used in several applications and a variety of cyber attacks can be performed on them using several tools. Some examples of these attacks include breaking the connection between the drone and the controller with deauthentication attacks, discovering a password or cryptographic key used in a communication protocol, gaining control of the drone through command/code injection, and attacks. This paper covers drone attacks by analyzing different components of the drone, including the remote controller and communication protocols. The main purpose is to provide an overview of the possible ways in which cyber attacks can be executed. This analysis concludes that drones, designed for diverse purposes, are vulnerable to a range of cyber attacks. The paper also reviews existing penetration testing methodologies for UAVs, which provide a logical framework for their realization. This review covers the different cyber attack methods and tools used against a UAV, intending to improve defense mechanisms.